Identifying patient-related predictors of permanent growth hormone deficiency - Mericq, Veronica; Iñiguez, German; Pinto, Graziella; Gonzalez-Briceño, Laura G.; Samara-Boustani, Dinane; Thalassinos, Caroline; Flechtner, Isabelle; Stoupa, Athanasia; Beltrand, Jacques; Besançon, Alix; Brabant, Séverine; Ghazal, Khaldoun; et al. (Frontiers in Endocrinology, 2023)
Objective Isolated childhood growth hormone deficiency (GHD) can persist into adulthood, and re-testing at the transition period is needed to determine whether continued growth hormone therapy is indicated. Here, our objective was to identify predictors of permanent GHD. Design Retrospective single-centre study of patients with childhood-onset GHD who were re-tested after adult height attainment. Methods Auxological, clinical, laboratory, and MRI data throughout follow-up were collected. Results We included 101 patients. At GH treatment initiation, age was 8.1 ± 0.4 years, height -2.25 ± 0.8, and BMI -0.27 ± 0.1 SDS. The 29 (28.7%) patients with persistent GHD had lower height SDS (-2.57 ± 0.1 vs. -2.11 ± 0.1, p<0.001) and mean GH peaks (8.4 ± 1.0 vs.13.2 ± 0.5 mIU/L, p<0.001) at GHD diagnosis; at adult height, they had lower IGF1 (232 ± 19.9 vs. 331 ± 9.1 ng/mL, p<0.001) and higher BMI SDS (-0.15 ± 0.27 vs. -0.73 ± 0.13, p<0.005). By multivariate analysis, the best predictive model included height and BMI SDS, both GH peaks, and MRI findings at diagnosis. Patients with height at diagnosis <-3 SDS had a 7.7 (95% IC 1.4-43.1, p=0.02) fold higher risk of persistent GHD after adjustment on BMI SDS. An abnormal pituitary region by MRI was the strongest single predictor (7.2 times, 95% CI 2.7-19.8) and after multivariate analysis adjustment for GH peaks and height SDS at diagnosis, the risk increased to 10.6 (1.8 - 61.3) times. Conclusions Height <-3 SDS at GHD diagnosis and pituitary MRI abnormalities should lead to a high index of suspicion for persistent GHD.